Requirements for User Experience Management - A Tertiary Study - Hinderks, Andreas; Domínguez Mayo, Francisco José; Escalona, María José; Thomaschewski, Jörg (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2024)
Today’s users expect to be able to interact with the products they own without much effort and also want to be excited about them. The development of a positive user experience must therefore be managed. We understand management in general as a combination of a goal, a strategy, and resources. When applied to UX, user experience management consists of a UX goal, a UX strategy, and UX resources. We conducted a tertiary study and examined the current state of existing literature regarding possible requirements. We want to figure out, what requirements can be derived from the literature reviews with the focus on UX and agile development. In total, we were able to identify and analyse 16 studies. After analysing the studies in detail, we identified different requirements for UX management. In summary, we identified 13 requirements. The most frequently mentioned requirements were prototypes and UX/usability evaluation. Communication between UX professionals and developers was identified as a major improvement in the software development process. In summary, we were able to identify requirements for UX management of People/Social, Technology/Artifacts, and Process/Practice. However, we could not identify requirements for UX management that enabled the development and achievement of a UX goal.
Keywords: agile methods; tertiary study; user experience; UX; IJIMAI